THE ADOPTION RATE OF SWEET CORN AS AN EFFORT TO INCREASE THE FARMERS' INCOME AND SUSTAINABLE AGRICULTURE DEVELOPMENT IN BALI - Nyoman Yudiarini; Luh Putu Kirana Pratiwi (Unmas Press, 2021)
The development of agriculture and the food crop sub-sector is directed at increasing food production to create food self-sufficiency. Sweet corn is one of the main secondary crops in Indonesia in terms of the entrepreneur and the use of the results, namely as a raw material for food and feed. The purpose of this study was to determine the level of adoption of sweet corn farmers in increasing farmers' income and to determine the factors that influence the level of adoption of sweet corn farmers to sustainable agricultural development in Subak of Padanggalak, Kesiman Kertalangu Village, Denpasar District, Denpasar City. Respondents in this study amounted to 25 people, with the census sampling method. The analysis in this study uses multiple linear analysis. The results showed that the level of adoption of sweet corn farmers on increasing income was influenced by six significant variables, namely: selection of superior seeds (X1), spacing (X2), irrigation (X3), use of organic fertilizers (X5), harvest (X7), and post-harvest handling (X8), while 2 variables that were not significant were the use of organic fertilizers (X4) and pest control (X6). Second, in the results of the study, the factors that influence the level of adoption of sweet corn farmers on sustainable agricultural development are age (X1), land area (X3), farming experience (X5), family members (X6) while the other two variables are not significant. namely education level (X2), land status (X4). It is recommended that the government through the Department of Agriculture is expected to continue to support farmers' activities in providing effective counseling to increase farmers' knowledge in the development of sweet corn, especially in the use of organic fertilizers and pest control.